BUDI DAYA JAMUR KUPING DENGAN INOVASI KAMAR KOSONG KOSAN MAHASISWA SEBAGAI KUMBUNG JAMUR - Suryani Suryani; Sariani Sariani; Femi Earnestly; Helga Yermadona; Rizalman Rizalman; Yustitia Akbar; Yuliesi Purnawati; Rahmawati Rahmawati (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The 7.8 magnitude earthquake and Tsunami issue that hit Padang City in 2009 caused Bung Hatta University to move its Campus to the Aie Pacah area, which is the green belt for the Tsunami. Results in the loss of income of people who have boarding rooms. Especially the RT 002RW 005 Housekeeping Group Wisma Wisma Warta Ulak Karang Padang, which located near the entrance of the campus. Because many boarding rooms left by students who moved to move near the new university. The purpose of this service is to increase community income by utilizing vacant rooms as a place/land for the cultivation of ear mushroom cultivation (Auricularia auricula). The method of carrying out this activity is training at the backlog maintenance stage, without preparing to make backlogs, the backlog is purchased from backlog artisans to accelerate the return of capital, bookkeeping training, business management training such as packaging, brands and business licenses. This community service program, in the third week, has been able to make money and increase the income of this group, replacing the boarding house/boarding house—fresh ear mushrooms sold per kg of Rp. 100,000 The group's ear mushroom brand is "S'ARICULA" (Fresh and Processed Ear Mushroom). This Community Service Program can solve problems with this group.